Antibacterial Activity Test of Aloe vera L. Leaf Extracts on Extended Spectrum ?-Lactamase (ESBL) Producing Bacteria from Surgical Site Infection Isolate - . Zakiatunnisa; . Maryani; Sigit Setyawan (Nexus Kedokteran Translasional, 2015)
Background: Surgical site infection is clinically defined as a discharge of purulent around wounds or cellulitis inside postoperative wounds. One of the factors that cause surgical site infections is the ESBL producing bacteria that developed a resistance towards most antibiotics. Aloe vera L. is known to possess a lot of antibacterials potent against various bacteria, either gram-positive or gram-negative. This research aims to prove the effects of the administration of Aloe vera L. leaf extracts towards the growth of ESBL producing bacteria from surgical site infection isolates. Method of research: This research was an experimental laboratory research (post test only with control group design) with sampling technique non-probability sampling ; consecutive sampling. The research was done in the UNS Faculty of Medicines Laboratory of Microbiology. Extraction of samples was done in the Dr. Moewardi Public Hospital Laboratory of Microbiology.The independent variable of this research was 70% ethanol extracts of Aloe vera L. leaf with concentrations of 25%, 50%, 75%, and 100%. The research subject was surgical site infection isolate ESBL producing bacteria, standardized with Mc Farland 0.5. Sensitivity test on the Muller-Hinton medium used the diffusion method with cefoperazon/sulbactam as positive control and aquades as negative control. The result of research was tested with Kruskal-Wallis testing method followed by Mann-Whitney testing method. Results: Kruskal-Wallis test results indicates a significant interception potential between two treatment groups (P = 0.000). Mann-Whitney test results indicates a significant difference of interception potentials on every treatment group, with the exception of the interception potential groups of 75% concentration extract and 100% concentration extract, no significant interception potential was found (P = 0.179). Conclusion: Aloe vera L. leaf extract proves to possess potential activity interception towards the growth of ESBL producing bacteria from surgical site infection isolates. The concentrations of Aloe vera L. leaf extract possess a positive correlation towards the interception potentials on surgical site infection ESBL producing bacteria. Keywords: Infection, postoperative wound, ESBL, Aloe vera.